Recovering the systemic redshift of galaxies from their Lyman alpha line profile. (6th April 2018) - Verhamme, A; Garel, T; Ventou, E; Contini, T; Bouché, N; Herenz, EC; Richard, J; Bacon, R; Schmidt, KB; Maseda, M; Marino, RA; Brinchmann, J; et al.
Abstract: The Lyman alpha (Ly α) line of Hydrogen is a prominent feature in the spectra of star-forming galaxies, usually redshifted by a few hundreds of km s −1 compared to the systemic redshift. This large offset hampers follow-up surveys, galaxy pair statistics, and correlations with quasar absorption lines when only Ly α is available. We propose diagnostics that can be used to recover the systemic redshift directly from the properties of the Ly α line profile. We use spectroscopic observations of Ly α emitters for which a precise measurement of the systemic redshift is available. Our sample contains 13 sources detected between z ≈ 3 and z ≈ 6 as part of various multi-unit spectroscopic explorer guaranteed time observations. We also include a compilation of spectroscopic Ly α data from the literature spanning a wide redshift range ( z ≈ 0–8). First, restricting our analysis to double-peaked Ly α spectra, we find a tight correlation between the velocity offset of the red peak with respect to the systemic redshift, V_peak^red, and the separation of the peaks. Secondly, we find a correlation between V_peak^red and the full width at half-maximum of the Ly α line. Fitting formulas to estimate systemic redshifts of galaxies with an accuracy of ≤100 km s −1, when only the Ly α emission line is available, are given for the two methods.